CRISPR-CAS System: Current Applications and Future Prospect - Adinda Adinda; Irene Ruth Saputra; Rachel Maya (Sriwijaya Journal of Medicine, 2024)
The CRISPR-Cas system is a revolutionary technology that has transformed gene editing and has the potential to revolutionize many fields. It is a bacterial immune system that can be programmed to recognize and cleave specific DNA sequences using Cas proteins and guide RNAs. This technology has numerous biotechnological and bioengineering applications and is simpler to design with high targeting efficiency and multiplex editing capability compared to older gene editing technologies. This review aims to explore the general application, impact on molecular biology and medicine, limitations, and future potential of the CRISPR-Cas system. With its potential to revolutionize medicine, agriculture, and environmental science, the CRISPR-Cas system is a powerful gene editing tool that offers hope for a wide range of applications.